PERTUMBUHAN DAN AKUMULASI MERKURI BERBAGAI JENIS TUMBUHAN YANG DITANAM DI MEDIA LIMBAH PENAMBANGAN EMAS DENGAN PERLAKUAN BERBAGAI TINGKAT KONSENTRASI MERKURI DAN KELAT AMONIUM TIOSULFAT - Juhaeti, Titi; Hidayati, N; Syarif, F; Hidayat, S (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Gold mining activities have recently increased in many areas. Contamination with heavy metals, mainly mercury due to illegal mine (PETI) have been in concern to residents around the area. One approach to remediate risks from some toxic metal pollutants is phytoextraction using hyperaccumulator plants. These remarkable plant species accumulate appreciable high concentrations of metals than do normal plants when the normal plants suffers yield reduction from metal phytotoxicity. Possible solution of using indigenous plants for phytoremediation has been studied. Performance of four selected plant species i.e Paspalum conjugatum, Centrosema pubescens, Commelina nudiflora and Mikania cordata were examined. In this study the plants were grown in PETI waste media contaminated with 25.733 ppm mercury (Hg), added with mercury (II) chloride (HgCl2) with different levels of concentrations i.e. 0 ppm Hg (HO), 10 ppm Hg (H10) and 20 ppm Hg (H20). To increase mercury uptake from the media, chelating agent, ammonium thiosulfat (NH4),S2O, was applied with concentration of 0 ppm (KO) dan 50 ppm (50). Plants biomass and mercury accumulation in plant shoots and roots were assessed at one and two months after treatments. The results showed that all of the plant species under study were highly tolerant to Hg. It was indicated by plant normal performances and high biomass production even in the highest level of Hg concentration and high Hg accumulation in the plant shoot and roots that reached 41.860 ppm in the shoot of P. conjugatum (H10 with chelate), 40.054 ppm in the shoot of C. pubescens (H20 no chelate),41.089 ppm in the shoot of C. nudiflora (H10 no chelate) and 42.610 ppm in the shoot of M. cordata (H10 no chelate). At the highest concentration levels of Hg under study there was no effects of toxicity on the plants, indicated by normal plant growth and high biomass production. Higher accumulation of Hg were found in the plants treated with higher level of Hg concentrations.